Spectroscopic study and energy transfer behavior of Gd3+ to Dy3+ for Li2O–MgO-Gd2O3–B2O3–Dy2O3 glasses for white emission material - I. Ullah (2020)
© 2020 The present study reports the Gd3+-sensitized Dy3+ luminescence and energy-transfer phenomenon, occurring in (B2O3)0.55-x (Li2O) 0.30(MgO)0.10(Gd2O3)0.05 (Dy2O3)x glasses, quenched by high-temperature melting. We study the Judd-Ofelt (JO) intensity parameters and radiative properties, determined by the absorption and emission spectra. The photoluminescence excitation of the Dy3+ at λem = 575 nm shows the existence of Gd3+ peaks (275 nm and 312 nm) while the emission spectra of the glasses reveal that among the four observed Dy3+ characteristics emissions (482 nm, 575 nm, 663 nm and 753 nm), only the λem = 575 nm enhances due to the excitation of the 4f7 state of the Gd3+ at λexc = 275 nm, an indicative of the effective energy transfer (ET) from the Gd3+ to the 4f-4f electric-dipole transition of the Dy3+. The ET predicts the sensitizer's luminescence decay and activator's luminescence growth, given the fact that an efficient yellow luminescence originates from the activtor's emitting centers. We determine the key parameters such as energy transfer efficiencies, transfer probabilities and average donor–acceptor distance by measuring the lifetimes from the sensitizer Gd3+ ions (λexc = 275 nm and λem = 312 nm) and the activator Dy3+ ions (λexc = 388 nm and λem = 575 nm). In addition, by using the Inokuti –Hirayama (IH) model, we find that the nature of the mechanism of the energy transfer between the Gd3+ and Dy3+ ions is predominantly the non-radiative phonon-assisted electric dipole–dipole. Lifetime of the samples decreases with increasing Dy3+ content (λexc = 388 nm and λem = 575 nm) which shows the resonance energy transfer (RET) within the Dy3+. This proposes that the luminescence and the energy transfer between the Gd3+ and the Dy3+ can be boosted up in the host glass, crucial for the persistent luminescence and spectral conversion/modification. The CIE color coordinates and CCT suggest that the present glasses are useful for white-light emission.